Interface Design of DJI Tello Quadcopter Flight Control - Fahmizal; Afidah , Danis; Istiqphara, Swadexi; Abu, Nur Syuhadah (Journal of Fuzzy Systems and Control, 2023)
Quadcopter is an unmanned, remote-controlled aircraft. This quadcopter has various types, in this study, the DJI Tello is used. The aim is to create a DJI Tello quadcopter flying control interface with Processing IDE, where the DJI Tello quadcopter will be controlled via a keyboard, joystick, and Graphical User Interface (GUI). Programmed through the Processing IDE, so the quadcopter can be controlled via the keyboard. The functions of some keys on the keyboard and joystick will be used to control the quadcopter's flying. To control these flying, several libraries available in the Processing IDE are required, while the GUI will function to read how the conditions of the quadcopter when the quadcopter and processing IDE are connected. The testing results show that the GUI can display the same position as the actual DJI Tello based on the data communication.